2021
DOI: 10.2147/ijgm.s326477
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Receptor Gene Polymorphisms and Risk of Atopic Dermatitis in Chinese Han Population

Abstract: Background: Studies investigated the associations between four Vitamin D receptor (VDR) common variations and interactions of gene-environment factors and atopic dermatitis (AD) in Chinese population are few. Methods: In this case-control study, 400 AD patients and 400 controls were genotyped for the FokI, TaqI, BsmI and ApalI variations of VDR genes by restriction fragment length polymorphism analysis. The associations between VDR genes and AD were assessed by univariate and multivariate logistic regression. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
1
3
0
1
Order By: Relevance
“…Several publications have reported associations between VDR gene polymorphisms, such as rs1544410 or rs2228570, and decreased vitamin D levels [33][34][35]. Additionally, rs2228570 has been associated with an increased risk of atopic dermatitis or allergic asthma in some studies [9,36,37]. A recent report even showed that the rs2228570 A allele increased the risk of allergic rhinitis [38].The results of our study support that the rs2228570 allele A is associated with decreased vitamin D levels in both patients with atopy and healthy subjects.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Several publications have reported associations between VDR gene polymorphisms, such as rs1544410 or rs2228570, and decreased vitamin D levels [33][34][35]. Additionally, rs2228570 has been associated with an increased risk of atopic dermatitis or allergic asthma in some studies [9,36,37]. A recent report even showed that the rs2228570 A allele increased the risk of allergic rhinitis [38].The results of our study support that the rs2228570 allele A is associated with decreased vitamin D levels in both patients with atopy and healthy subjects.…”
Section: Discussionsupporting
confidence: 84%
“…Studies have shown that VDR gene polymorphisms, such as rs7975232, rs1544410, and rs731236, may confer susceptibility to allergic diseases in certain populations [7]. Furthermore, several studies have demonstrated a significant association between VDR gene polymorphisms and asthma risk [8], or have indicated that rs2228570 could be associated with the risk of atopic dermatitis [9]. On the other hand, there is controversial data from various studies regarding the association of VDR SNPs with atopic conditions [10].…”
Section: Introductionmentioning
confidence: 99%
“…This metabolite is the ligand of the VDR, which in turn initiates a series of biological responses in bone metabolism, immunity, cell proliferation, and differentiation by binding to vitamin D response elements in DNA ( 79 ). Hence, rs2228570 has not only been associated with various skin diseases, such as chronic spontaneous urticaria (CSU) ( 80 ), atopic dermatitis (AD) ( 81 ), and leprosy ( 82 ), but has also been linked to an increased incidence risk and worse prognosis of different cancers, such as breast cancer ( 83 ), ovarian cancer ( 84 ), gastric cancer ( 85 ), hepatocellular carcinoma ( 86 ), papillary thyroid cancer ( 87 ), pancreatic cancer ( 88 ), and melanoma. Our results are consistent with previous studies using assay methods ( 89 ).…”
Section: Discussionmentioning
confidence: 99%
“…Несмотря на то, что уровень этого метаболита не достигал значений дефицита (<20 ng/ml), полученные результаты можно использовать для подбора индивидуальных доз витамина D при обязательном мониторинге концентрации данного метаболита. Исследования взаимосвязи концентрации 25-OH витамина D с вариантами полиморфизма гена VDR проводились различными авторами [15,16]. В частности, 11-летнее наблюдение за пациентами с низким уровнем 25-OH витамина D при однонуклеотидных заменах в гене VDR выявило их связь с развитием инфарктов, онкологических заболеваний и переломами шейки бедра.…”
Section:  результаты и обсуждениеunclassified